Kepemimpinan Inklusif Kepala Sekolah Dalam Menjaga Kerukunan dan Moderasi Beragama di Sekolah - Dannur Fuaddah; Rayi Ambarwati; Mu’rifatul Afidah; Kharisma Nila Rusiana; Theodora Indah Jati Indah Jati; Tamrin Fathoni (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The diversity of religions and cultures in Indonesia presents its own challenges in maintaining harmony in the school environment. The school principal has an important role as a leader who is able to create an inclusive and conducive atmosphere for the realization of religious harmony and moderation. This research aims to analyze the role of the principal's inclusive leadership in building harmony between religious communities and implementing the values of religious moderation in schools. The research approach used is descriptive qualitative with data collection through in-depth interviews, observation and literature study.. The research results show that school principals who implement inclusive leadership tend to be successful in creating an environment that respects differences and promotes interfaith dialogue. The policies taken, such as organizing interfaith activities and involving students in moderated discussions, are effective in instilling the values of tolerance and mutual respect. In addition, inclusive school principals are able to identify and resolve potential conflicts by prioritizing a fair and transparent approach. These findings show that inclusive leadership contributes significantly to creating a tolerant and harmonious school culture amidst diversity. This research concludes that the principal's inclusive leadership plays an important role in promoting religious moderation in schools. It is hoped that the results of this research can become a reference for school principals and education policy makers in designing strategies that support an inclusive, safe and tolerant school environment..